Evaluation of the performance, knowledge among IMCI Trained Health Workers in Primary Health Care Centers in Baquba City - Abdullah, Mazin Khalid; Bahir, Basim Hussein (Diyala Journal of Medicine, 2018)
Background: Conventional routine is not enough to improve child survival. The remedy of sick children is by controlling specific diseases. A strategy that was issued to control these diseases is integrated management of illness (IMCI) like those targeted at acute respiratory infection and diarrhea. Objective: To study aimed evaluation of the quality of IMCI Assessments among IMCI trained health workers program in primary health Care Centers in Baquba City. Patients and Methods: A cross sectional study was conducted in two sectors that cover health services in Baquba city from the period of 15 December 2015 to 1st June 2016. A convenient sample of 150 cases to evaluated performance of health workers was included in the study from the age of 2 month to 5 years and 55 from health workers to evaluated knowledge about IMCI program. Data collected by special designed questionnaire that adopted from world health organization (WHO). Results: The Result showed that 78.4 %of health providers were trained on IMNCH program. The performance of health workers were poor 33.3% of them checking temperature ,70% Checking the Weight of child ,24.6% asking for danger singes,71% asking about cough or difficult breathing ,30.6% asking for diarrhea ,72.6%asking for fever,22% evaluated ear problem,34%checking weight against growth chart ,20% looking for edema ,24.6% checking for sever wasting , 24% looking for palmer pallor ,88.6% asked about breastfeeding ,47% give advice on frequency of feeding 29.3% give instruction to bring back the child .while 69.2% of health workers answer correctly. Conclusion: Performances of health workers about program were poor while knowledge of health workers about IMNCH program was fair.